1999
DOI: 10.1046/j.1469-8137.1999.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling leaf expansion in a fluctuating environment: are changes in specific leaf area a consequence of changes in expansion rate?

Abstract: Leaf expansion rate varies with leaf temperature, photon flux density (PPFD), evaporative demand and soil water status. In most simulation models, it is calculated every day by multiplying the amount of carbohydrate available to leaves by specific leaf area (SLA). However, leaf expansion rate is considerably reduced by mild water deficits which do not affect photosynthesis, and is not affected by a reduction in the PPFD intercepted during rapid leaf expansion. Specific leaf area undergoes a several-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
1
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(153 citation statements)
references
References 25 publications
(34 reference statements)
11
135
1
6
Order By: Relevance
“…The approach used in this model is only valid when leaf growth is not source limited, which can only be achieved when agronomic management is optimized. Tardieu et al (1999) used a similar approach to simulate leaf area in sunflower (Helianthus annus L.) and maize (Zea mays L.).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The approach used in this model is only valid when leaf growth is not source limited, which can only be achieved when agronomic management is optimized. Tardieu et al (1999) used a similar approach to simulate leaf area in sunflower (Helianthus annus L.) and maize (Zea mays L.).…”
Section: Discussionmentioning
confidence: 99%
“…SLA varies in different environments, developmental stages, and strata of leaves within the canopy (Gunn et al, 1999;Lieth et al, 1986;Lugg and Sinclair, 1979). The mechanism of such flexibility in SLA is still not known and thus the variable often becomes the source of uncertainty in models that rely on SLA in simulating LAI (Tardieu et al, 1999). Lugg and Sinclair (1979) showed that SLA of the uppermost fully expanded soybean leaf varied from 0.333 cm 2 mg −1 at R1 to 0.146 cm 2 mg −1 at R6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLA P is determined by the sum of the processes which determine the surface expansion and net weight gain of individual leaves. Surface expansion is considered by Tardieu (1999) and net weight gain wil be considered here. Net weight gain by a leaf is a complex of many processes.…”
Section: General Conclusionmentioning
confidence: 99%
“…It may, though, be possible to account for the effect of stresses in early growth affecting later canopy characteristics by using time-delayed functions but introducing stress functions without describing the organs they actually apply to can be but empirical. The limitations in describing the effects of stresses early in crop/organ life may explain some of the difficulty in parameterisation of source-sink relationships through concepts such as specific leaf weight, specific leaf area, or harvest index (Birch et al 1998, Tardieu et al 1999.…”
Section: Existing Approachesmentioning
confidence: 99%